Internal Control System On Fraud Prevention Moderate By Bugis Cultural Values - Rahayu Wiliana; Febby Rachmadani; Syamsuddin Syamsuddin; Nadhirah Nagu; Achmad Fadel Farid (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze the influence of the internal control system on fraud prevention with Bugis cultural values as a moderator in the Sidenreng Rappang district government. The research population is the total number of ASNs in the Sidenreng Rappang district who manage special allocation funds for 13 agencies. Sampling was carried out through a non-probability sampling design by applying purposive sampling techniques; the sample obtained was 172 respondents. This research uses primary data, and data collection techniques are carried out by distributing questionnaires. Structural equation modelling (SEM), with Smart-PLS 3.0 software, is the statistical analysis used to test this research hypothesis. The research results show that implementing the internal control system positively and significantly affects the prevention of fraud, and Bugis' cultural values can strengthen the influence of the internal control system on fraud prevention efforts. The findings from this research can play a role in developing existing theories and provide references for institutions to reduce the risk of fraud.